2
$\begingroup$

The PDE is $xu_x-yu_y+yu=y$ .

The method of characteristics gives $\dfrac{dx}{x}=-\dfrac{dy}{y}=\dfrac{du}{y-yu}$

Then $x=-c_1y$ and thus $c_1=-\dfrac{x}{y}$ .

Then, I did $du=\dfrac{(y-yu)dy}{y}$ to try to solve for the second constant so that I can have that in terms of $f\left(-\dfrac{x}{y}\right)$ but I can't seem to do that.

$\endgroup$
1
$\begingroup$

$xu_x-yu_y+yu=y$

$yu_y-xu_x=y(u-1)$

$u_y-\dfrac{x}{y}u_x=u-1$

Follow the method in http://en.wikipedia.org/wiki/Method_of_characteristics#Example:

$\dfrac{dy}{dt}=1$ , letting $y(1)=1$ , we have $y=t$

$\dfrac{dx}{dt}=-\dfrac{x}{y}=-\dfrac{x}{t}$ , letting $x(1)=x_0$ , we have $x=\dfrac{x_0}{t}=\dfrac{x_0}{y}$

$\dfrac{du}{dt}=u-1$ , we have $u(x,y)=f(x_0)e^t+1=f(xy)e^y+1$

| cite | improve this answer | |
$\endgroup$
-1
$\begingroup$

$u \equiv w + 1\quad\Longrightarrow yw_{y} - xw_{x} + yw = 0$ $$ w = \phi\left(x\right)\varphi\left(y\right) \quad\Longrightarrow\quad y\varphi'\left(y\right) + y = x\phi'\left(x\right) = \mu = \mbox{constant} $$ $$ y\varphi'\left(y\right) + y = \mu \quad\Longrightarrow\quad \varphi'\left(y\right) = {\mu \over y} - 1 \quad\Longrightarrow\quad \varphi\left(y\right) = \mu\ln\left(y\right) - y + A\,,\ A: \mbox{constant} $$

$$ \phi'\left(x\right) = {\mu \over x} \quad\Longrightarrow\quad \phi\left(x\right) = \mu\ln\left(x\right) + B\,,\quad B: \mbox{constant} $$

$$ \begin{array}{|c|}\hline\\ \color{#ff0000}{\large\quad% u \color{#000000}{\ =\ } 1 + \left[\vphantom{\LARGE A}\mu\ln\left(x\right) + B\right] \left[\vphantom{\LARGE A}\mu\ln\left(y\right) - y + A\right] \quad} \\ \\ \hline \end{array} $$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.